The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1159/000334410
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Autonomy over Tobacco Scale in German

Abstract: Background/Aims: We investigated the psychometric properties of a German translation of the 12-item Autonomy over Tobacco Scale (AUTOS) among 1,195 eighth-grade students. Methods: Data for this study were collected as part of the fourth wave of data collection of the Smokefree Class Competition intervention in the Saxony-Anhalt region of Germany. Students from the control arm of the Smokefree Class Competition study who indicated that they had ever smoked ‘at least a few puffs’ on a cigarette were classified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The HONC (0.85–0.91) and AUTOS (0.91–0.96) scales also exhibited excellent reliability, AUTOS being the most reliable instrument. Wellman et al 49 subsequently tested the AUTOS in German adolescents; the German translation also demonstrated excellent reliability (0.96).…”
Section: Resultsmentioning
confidence: 99%
“…The HONC (0.85–0.91) and AUTOS (0.91–0.96) scales also exhibited excellent reliability, AUTOS being the most reliable instrument. Wellman et al 49 subsequently tested the AUTOS in German adolescents; the German translation also demonstrated excellent reliability (0.96).…”
Section: Resultsmentioning
confidence: 99%
“…In prior studies the AUTOS has demonstrated a single factor structure and excellent internal consistency (α = 0.91-0.96) with both adolescents and adults (DiFranza et al, 2009;Wellman et al, 2012). In adult smokers, the scale demonstrates concurrent validity against the FTCD, the HONC, the longest period of abstinence, days smoked per month, the percentage of time a smoker smokes because of momentary need, and the smoker's concern about Note: Item 1: "When I go too long without a cigarette, I get impatient."…”
Section: Discussionmentioning
confidence: 96%
“…Its face validity and other psychometric functions have been validated for the general U.S. population. 28 Because of the poor psychometric findings of the FTND for Korean women, the ATS was also used. To our knowledge, this measure had never been used with Korean Americans before the present study.…”
mentioning
confidence: 99%